Industrial policy 1996-2000 : a vision for the industrial development of Trinidad and Tobago (Ministry of Trade and Industry Port of SpainTT, 1996)
Concentrates on the manufacturing, small business and non-financial services sectors and provides direction for the development of these sectors over the medium term.
Keywords: INDUSTRIAL POLICY